İslam ve Batı / Islam and the West - Demircigil, Bayram (Journal of History Culture and Art Research, 2017)
Abstract The relationships between Islam and the West that has been become high on the agenda for the Islamic world and for our country throughout the last two centuries. It seems that this phenemonen will remain for a long time. Therefore, this topic is one of the major issues that needs to be analyzed extensively because it is mainly concerned with our country’s and Islamic world’s future. The author İbrahim Kalın addressed the historical account of the relationships between Islam and the West quite competently in his book titled “Islam and the West”. The major theme of this work is the way of thinking that there is still a common ground between the two civilisations which have a long history of conflicts, consequently the possibility of creating a peaceful atmosphere between both still exists. We could argue that one of the objectives that the author aimed to accomplish through this book is to provide an intellectual basis for the relations between Islam and the West as well as making a contribution to promoting and developing a dialog and reconcilitation between Muslims and the West. However, it might be an accurate conclusion that the general situation presented or suggestions made by depending on a few good examples in this book rely to a large extent on wishful thinking when we take into consideration that the relations between the two civilisations are based predominantly on prejudice, hostility and aggression along the history. Indeed, the author himself admits this fact in some of the phrases of the book. Öz İslam dünyasının, özellikle de ülkemizin birkaç asırdır gündemini meşgul eden ve bundan sonra da meşgul edecek gibi görünen İslam-Batı ilişkilerinin doğru ve objektif biçimde derinlemesine ele alınması gerekmektedir. Zira bu konu, İslam dünyasının ve ülkemizin geleceğini çok yakından ilgilendirmektedir. Bu bakımdan, İbrahim Kalın’ın söz konusu eseri büyük önem arz etmektedir. Bu eserin ana temasını, uzun bir tarihi geçmişi olan ve büyük çapta anlaşmazlıklar ve çatışmalar silsilesinden oluşan İslam-Batı ilişkilerinde bazı uzlaşı noktalarının da bulunduğu ve ikisi arasında sağlıklı bir diyalog zemininin oluşturulmasının mümkün olduğu, dolayısıyla bu iki medeniyet arasındaki kavga halinin aslında kaçınılmaz bir durumu yansıtmadığı düşüncesi oluşturmaktadır. Bu temelden hareketle yazar, eserinde İslam ve Batı arasındaki ilişkiler için entelektüel bir zemin oluşturmayı ve iki medeniyet arasında diyalog ve barış ortamının geliştirilmesine katkı sunmayı amaçlamaktadır. İbrahim Kalın’ın birkaç örnekten yola çıkarak iki medeniyet arasında bir uzlaşı zemini oluşturulması yönündeki çabasının, aktüel durum dikkate alındığında, pek gerçekçi görünmediği ve bir temenniden ibaret kalacağı söylenebilir. Aslında yazar da satır aralarında bu gerçeği itiraf etmektedir. Bununla birlikte yazarın tarihsel süreç içinde İslam-Batı ilişkilerini güzel bir üslupla ele aldığı böyle bir çalışma, bir iyi niyet göstergesi olarak son derece değerlidir.